Analysis of psychological factors which interfere in soccer athletes’ behaviour - Constanza Pujals; Lenamar Fiorese Vieira (Revista da Educação Física)
The aim of this study is to analyze the psychological factors which interfere in soccer athletes’s behaviour, juvenile and infant categories. 40 athletes from a soccer school in Maringá – PR were studied and the instruments used were: inventories, interviews, questionnaires and research diary. Data were collected individually and in group. Intervention occurred for 12 months through observation, evaluation and showed the following factors: motivation, anxiety, aggression and self confidence. Results pointed out that the positive emotions expressed by the athletes were good mood, happiness, relaxation, interest in improving and hope while negative emotions were anxiety, rage, aggressiveness, low self-confidence, lack of motivation, insecurity, feeling of failure, pessimism and group instability. Relatives and coach were also generating factors of stress and anxiety. Thus, this sporting context shows that the sports psychology seems to be highly efficient to reduce anxiety and agression indexes as well as to increase motivation and self-confidence, demonstrating the importance of psychological preparation for sporting training.